Barriers to Improving the Environmental Performance of Construction Waste Management in Remote Communities. (2017) - Crawford, Robert H.; Mathur, Deepika; Gerritsen, Rolf
Abstract: The construction sector represents one of the most significant contributors to global waste production and is responsible for over 30% of the waste that ends up in landfill. Sending construction waste to landfill results in a broad range of environmental consequences including: degradation of land, habitat destruction, contamination of soil and groundwater, and release of methane. There is a growing awareness of the need to divert construction and demolition (C&D) waste from landfill for reuse or recycling. This helps maximise the value of the resources embodied in these materials and reduce the demand for virgin raw materials and the associated environment effects resulting from their extraction, processing and manufacture. However, diversion of C&D waste to reuse or recycling in remote communities can be difficult and costly. This poses a significant challenge for improving the environmental performance of construction waste management in these communities. A housing refurbishment project in Alice Springs, a remote town in central Australia, was used to identify the barriers associated with improving the environmental performance of construction waste management in remote communities. This study considers the materials removed as part of the demolition phase of the project. Material types and quantities were documented and on-site and off-site waste management practices observed. Reasons for waste management decisions were recorded. The study identified a range of barriers to improving the environmental performance of construction waste management in remote communities. These include cost and time associated with on-site waste management, industry culture, lack of education, competing project priorities, and lack of financial incentive. Greater incentives to encourage the diversion of C&D waste from landfill are needed, in particular. This and other strategies for improving construction waste management practices in remote communities must be targeted at the context of individual communities though, due to their unique characteristics.